Does the Method of Castration Affect Calf Performance? - Trey Warnock; Matt Hersom; Todd Thrift (EDIS)
This 4-page fact sheet discusses the purpose of castration in male calves as well as the different methods used to castrate. Most methods of castration cause a certain amount of pain and stress for calves, which can affect calf performance. UF/IFAS researchers recently tested different methods of castration in calves to determine the effects of each method on calf health and performance. This publication presents these results. Written by Trey Warnock, Matt Hersom, and Todd Thrift, and published by the UF Department of Animal Sciences, December 2013.